Health psychology - Taylor, Shelley E. (McGraw-Hill, 2006)
The sixth edition of this trusted text continues to set the standard for the Health Psychology market. One of the foremost researchers in health psychology, author Shelley Taylor incorporates the latest research findings in the field; the result is a text that conveys the increasing sophistication and complexity of the connection between the mind and the body, in an accessible and exciting manner. The flexible organization and emphasis on many relevant areas of psychology make Health Psychology appropriate for courses in Health Psychology, Health and Human Behavior, and allied health and pre-med/pharmacy programs.